1961
DOI: 10.1530/acta.0.0380432
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alloxan Diabetes on the Reproductive System of Young Male Rats

Abstract: Male rats 23 days of age were rendered diabetic by subcutaneous injections of alloxan. Diabetes was determined one week later on the basis of urine sugar concentration. At regular intervals following treatment animals were sacrificed and the testes, seminal vesicles and prostate gland removed for histological study. Severe diabetes resulted in failure of descent of the testes, failure of development of the germinal epithelium and castrate-type accessory organs. A more moderate diabetic condition resulted in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

1975
1975
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 7 publications
2
14
0
Order By: Relevance
“…The occurrence of glycosuria is one of the determining factors in the identification of diabetes type I; it has been demonstrated both in animals submitted to different diabetogenic drugs and in spontaneously diabetic animals (Hunt and Bailey, 1961;Makino et al, 1980;Ader et al, 1998). Thus, it may be concluded that both the mice submitted to chemical induction with alloxan and the mice with spontaneously generated diabetes (NOD) manifested diabetes in an effective manner, confirming the validity of the experimental model.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The occurrence of glycosuria is one of the determining factors in the identification of diabetes type I; it has been demonstrated both in animals submitted to different diabetogenic drugs and in spontaneously diabetic animals (Hunt and Bailey, 1961;Makino et al, 1980;Ader et al, 1998). Thus, it may be concluded that both the mice submitted to chemical induction with alloxan and the mice with spontaneously generated diabetes (NOD) manifested diabetes in an effective manner, confirming the validity of the experimental model.…”
Section: Discussionmentioning
confidence: 63%
“…Particularly important among these changes was stromal tissue hypertrophy with the occurrence of an inflammatory cell infiltrate, in addition to intense volumetric atrophy of secretory epithelial cells, with a predominance of the cytoplasmic portion and nuclear deformity in the coagulation gland. Previous studies on the ventral lobe of the prostate of diabetic rats and mice demonstrated atrophy of the secretory epithelial cells and enlargement of the stromal region (Hunt and Bailey, 1961;Jackson and Hutson, 1984;Cagnon et al, 2000). Several experiments carried out to analyze accessory sex glands, including the coagulation gland, under androgen deprivation showed a disorganized morphology of the secretory epithelium and the stroma, with an increase in smooth muscle cells and collagen, and elastic fibers in the ventral lobe of the prostate of castrated rats (Aumü ller, 1977;Mariotti et al, 1987;De Carvalho and Line, 1996;Kiess and Gallaher, 1998).…”
Section: Discussionmentioning
confidence: 91%
“…Recently, atten tion has also been paid to the dysfunction o f the male reproductive organs in experimental and spontaneous diabetic conditions. Testicular lesions in diabetic patients have been described by Schoffling et al (1963) and the deleterious effects o f alloxan diabetes on the germinal epithelium o f male rats have been reported by several investigators (Soulairac et al, 1948;Hunt and Bailey, 1961;Federlin et al, 1965;Schoffling et al, 1967). Hunt and Bailey (1961) also showed that following the induction o f alloxan diabetes in immature male rats, tire accessory sex glands remained in a state resembling that occurring after castration.…”
Section: Introductionmentioning
confidence: 89%
“…Testicular lesions in diabetic patients have been described by Schoffling et al (1963) and the deleterious effects o f alloxan diabetes on the germinal epithelium o f male rats have been reported by several investigators (Soulairac et al, 1948;Hunt and Bailey, 1961;Federlin et al, 1965;Schoffling et al, 1967). Hunt and Bailey (1961) also showed that following the induction o f alloxan diabetes in immature male rats, tire accessory sex glands remained in a state resembling that occurring after castration. On the other hand, Lostroh (1968Lostroh ( , 1971 has demonstrated in vitro the synergism o f insulin and testosterone in tire maintenance o f the growth and secretory activity o f cultured prostatic epithelium.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation